Management of Helicobacter pylori in Patients with Immune Thrombocytopenia - Vanegas, Yenny Alejandra Moreno; Vishnu, Prakash (Hämostaseologie, 2019)
There is an association between Helicobacter pylori infection and immune thrombocytopenia (ITP), and few studies have suggested that eradicative treatment of H. pylori infection may improve platelet counts in patients with ITP. Conventional treatments for ITP include immunosuppressive agents, and more recently thrombopoietic agents. However, based on clinical reports of association between H. pylori and ITP, several medical societies increasingly suggest detection and eradication of H. pylori as a treatment for ITP. In this article, we reappraise recent medical literature to determine the effectiveness of platelet response after treatment of H. pylori infection in patients with ITP. We searched two online databases (MEDLINE and Google Scholar) for full articles published between January 2008 and May 2018, and found a total of 11 studies that presented data and outcomes of treatment of H. pylori infection in ITP patients. All the studies administered triple therapy (amoxicillin 500 mg, clarithromycin 250 mg and a proton-pump inhibitor each given twice daily for either 7- or 14-day course) for eradication of H. pylori. Median overall platelet response ranged from 27 to 69.2% with a complete response rate ranging from 0 to 65.4% and a partial response rate ranging from 0 to 29.4%. Although there is variability in the effectiveness between different populations, it appears to be of benefit to ITP patients with concomitant H. pylori infection when treated with triple therapy. However, further studies to understand the pathogenesis of H. pylori-associated ITP is necessary for the development of new therapeutic approaches for ITP.
Keywords: immune thrombocytopenia; Helicobacter pylori; antibiotic